Agricultural advisory services in Tajikistan: Private sector role - Aliev, Jovidon; Khakimov, Parviz; Ashurov, Timur; Goibov, Manuchehr (International Food Policy Research Institute, 2025)
Agricultural advisory services (AAS) may play a crucial role in supporting Tajikistan’s food security and rural development by helping farmers to increase productivity, adopt new technologies, and access to the markets. Despite their significance, AAS remain underdeveloped with limited coverage and accessibility. Strengthening AAS through government support, private sector engagement, and in partnership with NGOs can address the challenges and contribute to sustainable growth of the sector.